1990
DOI: 10.1007/bf00842787
|View full text |Cite
|
Sign up to set email alerts
|

European multicentre study on melanoma immunoscintigraphy by means of99mTc-labelled monoclonal antibody fragments

Abstract: A total of 493 melanoma patients were investigated by 20 European nuclear medicine departments by means of the same 99mTc-labelled immunoradiopharmaceutical and the same immunoscintigraphy (ISG) protocol. (i) No chemical or clinical toxicity was detected during or following the studies. (ii) Positive results were obtained in 287/363 (79%) patients (321 carrying known lesions and 42 carrying previously occult lesions): in 231 (80%) of them, 402/402 lesions were imaged; in the remaining 56 ISG-positive patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 15 publications
0
12
1
1
Order By: Relevance
“…First, CSPG4 is highly expressed on malignant cells, but has a restricted distribution in normal tissues (32). This distribution accounts for the selective targeting of malignant lesions when radiolabeled CSPG4-specific mAbs have been injected in patients with CSPG4 + melanoma lesions (33, 34). Furthermore, these results altogether provide an explanation for the lack of side effects in patients with melanoma who developed CSPG4-specific antibodies following immunization with CSPG4 mimics, in spite of an apparent antitumor effect (7, 8).…”
Section: Discussionmentioning
confidence: 99%
“…First, CSPG4 is highly expressed on malignant cells, but has a restricted distribution in normal tissues (32). This distribution accounts for the selective targeting of malignant lesions when radiolabeled CSPG4-specific mAbs have been injected in patients with CSPG4 + melanoma lesions (33, 34). Furthermore, these results altogether provide an explanation for the lack of side effects in patients with melanoma who developed CSPG4-specific antibodies following immunization with CSPG4 mimics, in spite of an apparent antitumor effect (7, 8).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials in a large number of patients with melanoma have shown that injection of radiolabelled anti-HMW-MAA MAbs visualizes approximately 60% of melanoma lesions Siccardi et al, 1986Siccardi et al, , 1990. This result emphasizes the need for approaches which increase the sensitivity of immunoscintigraphy with radiolabelled antiWe have shown that affinity chromatography on some, though not all, insolubilized anti-idiotypic MAbs represents an efficient method for purifying immunoreactive MAbs from radiolabelled MAb preparations (Temponi et a[., 1990).…”
Section: In Nude Mice Bearing Human Melanoma Lesionsmentioning
confidence: 83%
“…Each patient in the sample initially underwent traditional immunoscintigraphy with MoAb 225 28S radiolabelled with mTc, and a three step immunoscintigraphy 1 week later. All patients underwent enucleation.…”
Section: Patientsmentioning
confidence: 99%